Brewer's yeast polysaccharides — A review of their exquisite structural features and biomedical applications. (1st February 2022) - Bastos, Rita; Oliveira, Patrícia G.; Gaspar, Vítor M.; Mano, João F.; Coimbra, Manuel A.; Coelho, Elisabete
Abstract: Recent advances on brewer's yeast cell wall polysaccharides have unraveled exquisite structural features and diverse composition with ( β 1→3), ( β 1→6), ( α 1→4), ( β 1→4)-mix-linked glucans that are recognized to interact with different cell receptors and trigger specific biological responses. Herein, a comprehensive showcase of structure-biofunctional relationships between yeast polysaccharides and their biological targets is highlighted, with a focus on polysaccharide features that govern the biomedical activity. The insolubility of β -glucans is a crucial factor for binding and activation of Dectin-1 receptor, operating as adjuvants of immune responses. Contrarily, soluble low molecular weight β -glucans have a strong inhibition of reactive oxygen species production, acting as antagonists of Dectin-1 mediated signaling. Soluble glucan-protein moieties can also act as antitumoral agents. The balance between mannoproteins-TLR2 and β -glucans-Dectin-1 receptors-activation is crucial for osteogenesis. Biomedical applications value can also be obtained from yeast microcapsules as oral delivery systems, where highly branched ( β 1→6)-glucans lead to higher receptor affinity. Graphical abstract: Unlabelled Image